Revealing the Mutational Spectrum in Southern Africans With Amyotrophic Lateral Sclerosis. (February 2022) - Nel, Melissa; Mahungu, Amokelani C.; Monnakgotla, Nomakhosazana; Botha, Gerrit R.; Mulder, Nicola J.; Wu, Gang; Rampersaud, Evadnie; van Blitterswijk, Marka; Wuu, Joanne; Cooley, Anne; Myers, Jason; Rademakers, Rosa; et al.
Abstract : Background and Objectives: To perform the first screen of 44 amyotrophic lateral sclerosis (ALS) genes in a cohort of African genetic ancestry individuals with ALS using whole-genome sequencing (WGS) data. Methods: One hundred three consecutive cases with probable/definite ALS (using the revised El Escorial criteria), and self-categorized as African genetic ancestry, underwent WGS using various Illumina platforms. As population controls, 238 samples from various African WGS data sets were included. Our analysis was restricted to 44 ALS genes, which were curated for rare sequence variants and classified according to the American College of Medical Genetics guidelines as likely benign, uncertain significance, likely pathogenic, or pathogenic variants. Results: Thirteen percent of 103 ALS cases harbored pathogenic variants; 5 different SOD1 variants (N87S, G94D, I114T, L145S, and L145F) in 5 individuals (5%, 1 familial case), pathogenic C9orf72 repeat expansions in 7 individuals (7%, 1 familial case) and a likely pathogenic ANXA11 (G38R) variant in 1 individual. Thirty individuals (29%) harbored ≥1 variant of uncertain significance; 10 of these variants had limited pathogenic evidence, although this was insufficient to permit confident classification as pathogenic. Discussion: Our findings show that known ALS genes can be expected to identify a genetic cause of disease in >11% of sporadic ALS cases of African genetic ancestry. Similar to European cohorts, the 2 most frequent genes harboring pathogenic variants in this population group are C9orf72 and SOD1 .